Forecasting performance of the P-star model: The case of Indonesia - Tang, M.M.-J.; Puah, Chin-Hong; Affendy Arip, M.; Dayang Affizzah, Awang Marikan (International Academy of Business and Economics, 2015)
This paper investigated the linkage between money supply and inflation in Indonesia by adopting the PStar model. Both the simple-sum and Divisia monetary aggregates were employed to compare their relative performance in terms of inflation forecasting. The empirical findings revealed that the P-Star model performed well in tracking inflation in Indonesia. In addition, the Divisia M2 model returned better results with greater prediction information on inflationary movement in Indonesia.